AB0997 Ultrasonographic evaluation of anterior knee pain in young adults. (15th June 2017) - Negm, AA; Khairy, M; Hasseb, A; Abbas, K
Abstract : Objectives: The Primary outcome of the present work is to detect type and frequency of Ultrasonographic changes in patients with anterior knee pain. Secondary outcome is to determine the role of MSUS in early detection of causes of anterior knee pain (AKP). Methods: Sixty patients with AKP and 20 sex and age matched healthy control were included in this study obtained from the outpatient of Physical Medicine and Rheumatology Department of El Hussein and Bab El - Sharia university hospitals. Inclusion criteria: age between 20–40. Exclusion criteria: Trauma, Crystal induced arthritis, connective tissue diseases (RA, SLE, SpA), chronic liver or kidney disease and previous surgery. Full medical history and clinical examination as well as WOMAC, knee Conventional Radiography and Musculoskeletal Ultrasonography (MSUS) were done to all patients. Bilateral MSUS examination of the following common sites: Insertion of quadriceps tendon, Ligamentum patellae and Anterior aspect of the knee from medial to lateral. According to EULAR guide lines for musculoskeletal ultrasonography. Results: The mean duration of knee pain in patients group was 11.42±9.134 months. ESR, CRP and WOMAC were higher in patients group (p<0.01). MSUS showed significantly more frequent Supra-patellar and Infra-patellar bursitis in patients than control group (p=0.000). patients had higher frequency of cartilage clarity loss (p=0.039) as well as lower cartilage thickness than control, 2.28±0.258 vs 2.73±0.261 mm respectively (P=0.000, 95% CI: 0.31 to 0.58) Conclusions: The degree of Knee pain, measured by WOMAC, is positively correlated with inflammatory biomarkers (ESR and CRP) in patients with Anterior knee pain. MSUS revealed a positive correlation between Femoral Articular Cartilage thickness and the periarticular tendon- thickness, namely Patellar origin, patellar insertion and Quadriceps insertion. Interestingly, our data present an evidence of the negative impact of the duration of knee pain over Femoral Articular Cartilage thickness as well as Patellar origin thickness. (FAC thickness get worse with longer duration of pain) References: Backhaus, M., et al. Guidelines for musculoskeletal ultrasound in rheumatology. Annals of the rheumatic diseases 60.7 (2001): 641–649. Disclosure of Interest: None declared